ANALISIS TINGKAT KEBERLANJUTAN SMART CITY PADA DIMENSI SMART LIVING DI KOTA SURAKARTA - Berlian Berlian; S Agus Santoso (Jurnal Administrasi Publik, 2026)
This study analyzes the sustainability level of smart city implementation, focusing on the smart living dimension in Surakarta City. A mixed-method approach with a concurrent embedded design was employed, integrating quantitative and qualitative research simultaneously. Quantitative analysis utilized scoring methods based on SNI ISO 37122:2019, as published by the National Standardization Agency (BSN). Qualitative analysis applied the interactive model developed by Miles, Huberman, and Saldana (2014). Data collection involved in-depth interviews with seven relevant government agencies and a review of secondary documentation. Data validity was ensured through triangulation of sources and techniques. The findings indicate that the sustainability level of smart living in Surakarta City is at Level 3 (Intermediate Smart City), with a final score of 40.73%. This result demonstrates that the city has implemented integrated information service processes using open data accessible to the public. Recommendations for each sub-dimension are as follows: for the harmony sub-dimension, expand digital surveillance camera coverage, particularly in 14 underserved urban villages; for the mobility sub-dimension, identify inclusive development priorities to enhance accessible infrastructure for persons with disabilities; and for the health sub-dimension, strengthen digital telemedicine infrastructure and increase public awareness of air and water quality monitoring systems.